SIGNIFICANCE AND MULTIPLE VALUES OF THE RHOMBUS IN TRADITIONAL ROMANIAN ART - Cazac, V.; Adascaliţa, L. (Art and Design, 2023)
The purpose of the study is related to the identification and analysis of the significance and multiple values of the rhombus in the Romanian art, considering from its frequent perpetuation in the traditional art. Methodology. The study is founded by the application of direct-descriptive observation methods, exploratory methods, structural, comparative, culturological-historical, artistic, inductive and deductive analysis. The substantiation of the arguments was based on the multicriterial analysis of the bibliographic sources of reference published on this subject. Results. There were analyzed the interpretation of the subject in different bibliographical sources, analyzed the approach of the Rhombus from the oldest sources that attest its presence both as a synthesis of the form and as an ornamental element, there were analyzed the meanings attributed to the Rhombus as a representative visual identity element, there were analyzed the ways of visual representation of the Rhombus and were structured, it was observed and analyzed the presence of the Rhombus in the various pieces of interior textiles Romanian. Scientific novelty. The evaluation of the importance of the Rhombus for the intangible cultural heritage, of the frequency of finding the Rhombus in the traditional art objects, the awareness regarding the capitalization of this important element found in the traditional Romanian culture that denotes the arguments of the spiritual aspirations of identity. Practical significance. The practical importance is offered by the knowledge of the forms of representation of the Rhombus and of the meanings it denotes in one interpretation or another constituting reconnosable coded visual narratives. The paper presents the results of the study carried out within the State Program 20.8009.0807.17 REVICULT "Education for the revitalization of the national cultural heritage through the traditional processing technologies used in the Republic of Moldova, in the context of multiculturalism, diversity and European integration".